0
$\begingroup$

Suppose $y=f(x)$. Calcuate $$\frac{d}{dy} \frac{1}{x}.$$

My effort: If we had the inverse $x=f^{-1}(y)$, then we could do $$\frac{d}{dy} \frac{1}{x}= \frac{d}{dy} \frac{1}{f^{-1}(y)}$$ But, how do we do it if we don't have $f^{-1}(y)$?

$\endgroup$
4
$\begingroup$

Power rule, chain rule:

$$\frac{d}{dy}\frac{1}{x} = \frac{-1}{x^2}\frac{dx}{dy} = \frac{-1}{x^2dy/dx} = \frac{-1}{x^2f'(x)}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.